2005
DOI: 10.1029/2004jc002861
|View full text |Cite
|
Sign up to set email alerts
|

The mean circulation of the southwestern Mediterranean Sea: Algerian Gyres

Abstract: This is a study about the general circulation of the southwestern Mediterranean Sea based on observations of currents carried out in the southwestern Mediterranean Sea in the framework of the Mass Transfer and Ecosystem Response (MATER) program (EEC/MAST3 program). From July 1997 to August 2002, profiling floats (MEDPROF experiment), isobaric floats (LIWEX experiment), and moored current meters (ELISA experiment) give evidence of two large-scale barotropic cyclonic circulations, the here-called Western and Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
70
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 38 publications
15
70
0
Order By: Relevance
“…12). This first anomaly corresponds to the Eastern Algerian Gyre (EAG) already described by Testor et al, (2005). This gyre has an almost stable position during our investigation period, only moving seaward after one month and approaching the Algerian coast once again at the end of October.…”
Section: Geostrophic and Ageostrophic Velocitiessupporting
confidence: 61%
“…12). This first anomaly corresponds to the Eastern Algerian Gyre (EAG) already described by Testor et al, (2005). This gyre has an almost stable position during our investigation period, only moving seaward after one month and approaching the Algerian coast once again at the end of October.…”
Section: Geostrophic and Ageostrophic Velocitiessupporting
confidence: 61%
“…Thus, the effect of the main advective spreading (i.e., without the eddy circulation) tends to propagate WMDW toward the Strait of Gibraltar rather than toward the Channel of Sardinia. But a part of it is trapped into the eastern Algerian gyre by closed f/H isocontours constraint [ Testor et al , 2005], where f is the planetary vorticity and H the water depth. On the contrary, we showed that the deep eddy circulation south of the Balearic Islands toward the center of the Algerian subbasin is able to transport WMDW characteristics to the east toward the Channel of Sardinia.…”
Section: Discussionmentioning
confidence: 99%
“…The Atlantic Water enters the Mediterranean at the Strait of Gibraltar in the surface layer and flows around the sea in a cyclonic path of more or less stable boundary currents, producing meanders and eddies [64]. The general surface circulation in the Mediterranean is strongly constrained by the wind [65] and by the complex bathymetry [66].…”
Section: Methodsmentioning
confidence: 99%